Pharmacological Targeting of CSF1R Inhibits Microglial Proliferation and Aggravates the Progression of Cerebral Ischemic Pathology - Hou, Boru; Jiang, Cheng; Wang, Dong; Wang, Gang; Wang, Zening; Zhu, Miaojuan; Kang, Yuchen; Su, Jiacheng; Wei, Pengfei; Ren, Haijun; Ju, Furong (Frontiers in Cellular Neuroscience, 2020)
Ischemic stroke can induce rapid activation of the microglia. It has been reported that the microglia’s survival is dependent on colony-stimulating factor 1 receptor (CSF1R) signaling and that pharmacological inhibition of CSF1R leads to morphological changes in the microglia in the healthy brain. However, the impact of CSF1R inhibition on neuronal structures and motor ability after ischemia–reperfusion remains unclear. In this study, we investigated microglial de-ramification, proliferation, and activation after inhibition of CSF1R by a tyrosine kinase inhibitor (ki20227) in a mouse model of global cerebral ischemia induced by bilateral common carotid artery ligation (BCAL). In addition to microglial morphology, we evaluated the mRNA expression of cytokines, chemokines, and inflammatory receptors. Our results show that pharmacological inhibition of CSF1R in ischemic mice resulted in the blockade of microglial proliferation and a shift in microglial morphology reflected by excessive de-ramification and a more activated phenotype accompanied by an enhanced innate immune response. Furthermore, we show that pharmacological inhibition of CSF1R in ischemic mice resulted in the aggravation of neuronal degeneration and behavioral impairment. Intravital two-photon imaging revealed that although pharmacological inhibition of CSF1R did not affect the recovery of dendritic structures, it caused a significant increase in spine elimination during reperfusion in ischemic mice. These findings suggest that pharmacological inhibition of CSF1R induces a blockade of microglial proliferation and causes acute activation of the microglia accompanied by a severe inflammatory response. It aggravates neuronal degeneration, loss of dendritic spines, and behavioral deficits after transient global cerebral ischemia.